2017
DOI: 10.1161/jaha.117.006416
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Reveals Inflexibility of the Diaphragm in an Animal Model of Patients With Obesity‐Driven Heart Failure With a Preserved Ejection Fraction

Abstract: BackgroundRespiratory muscle weakness contributes to exercise intolerance in patients with heart failure with a preserved ejection fraction (HFpEF)—a condition characterized by multiple comorbidities with few proven treatments. We aimed, therefore, to provide novel insight into the underlying diaphragmatic alterations that occur in HFpEF by using an obese cardiometabolic rat model and further assessed whether exercise training performed only after the development of overt HFpEF could reverse impairments.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 29 publications
(93 reference statements)
7
52
0
Order By: Relevance
“…The recent study by Miyagi et al [8] clearly highlights that more data are urgently needed in relation to HFpEF. We have confirmed that rats with HFpEF similarly demonstrate significant impairments to contractile function in isolated diaphragm fibers [15,16], with impaired mitochondrial complex I function appearing as one key mechanism. Importantly, this was attenuated by endurance exercise training [16].…”
Section: Takedownsupporting
confidence: 70%
“…The recent study by Miyagi et al [8] clearly highlights that more data are urgently needed in relation to HFpEF. We have confirmed that rats with HFpEF similarly demonstrate significant impairments to contractile function in isolated diaphragm fibers [15,16], with impaired mitochondrial complex I function appearing as one key mechanism. Importantly, this was attenuated by endurance exercise training [16].…”
Section: Takedownsupporting
confidence: 70%
“…secondary prevention). In this study, we used a recently established cardiometabolic obese-driven rat model of HFpEF [3,12,13]. The model closely resembles a typical patient phenotype, where cardiac impairments and exercise intolerance are underpinned by numerous comorbidities including obesity, type II diabetes, hypertension, and kidney dysfunction [14,15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Procedures and experiments in this study were approved by the Norwegian Animal Research Authority, in accordance the European Directive 2010/63/EU. A full description of the present study design and animal cohort as well as the methods employed were recently described elsewhere [3]. Briefly, obese diabetic Zucker fatty/Spontaneously hypertensive heart failure F1 hybrid (ZSF1) rats (Charles River, Kingston, US) were used as a model to induce HFpEF, which occurs by 20 weeks of age [3,12,13].…”
Section: Study Design and Animal Model Of Hfpefmentioning
confidence: 99%
See 2 more Smart Citations